Theatre Institutions in Crisis European Perspectives - Balme, Christopher; Fisher, Tony (Taylor & Francis, 2021)
Theatre Institutions in Crisis examines how theatre in Europe is beset by a crisis on an institutional level and the pressing need for robust research into the complex configuration of factors at work that are leading to significant shifts in the way theatre is understood, organised, delivered, and received. Balme and Fisher bring together scholars from different disciplines and countries across Europe to examine what factors can be said to be most common to the institutional crisis of European theatre today. The methods employed are drawn from systems theory, social-scientific approaches, economics and statistics, theatre and performance, and other interpretative approaches (hermeneutics), and labour studies. This book will be of great interest to researchers, students, and practitioners working in the fields of performance and theatre studies. It will be particularly relevant to researchers with a particular interest in European theatre and its networks.